Analisis Unsur Stem Pada Pemuatan Batu Bata Tradisional Dan Press Dengan Konsep Termodinamika - Aisyaningrum Maharani Devina Larasati Prapsetyo; Agung Prapsetyo (JURNAL TEKNIK SIPIL PERTAHANAN, 2026)
The brick industry is a rapidly growing manufacturing sector in Magelang Regency. Clay and sand are the primary materials in the manufacturing process, which involves excavation, mixing, molding, drying, and firing. This study aims to analyze the application of thermodynamic laws to the brick-making process and to identify the STEM (Science, Technology, Engineering, and Mathematics) elements contained therein. The research method used is a qualitative method, with direct observation techniques and strengthened by interviews and literature studies. The results show that the brick-firing process is related to the Second Law of Thermodynamics, namely that heat energy flows directly from a high-temperature object to a low-temperature object through radiation, convection, and conduction mechanisms. The scientific element is reflected in the application of the concept of heat transfer; the technological element in the use of presses and grinding machines; the engineering element in the design of the brick arrangement in the kiln; and the mathematical element in the calculation of the heat required in the firing process. This study contributes to understanding the integration of physics concepts with traditional industrial practices and its implications for improving the quality of brick products.